Preformed composite dental crown, method of production and use thereof

The preformed composite crown made of chemical compositions of nanofillers and resin matrix solves the shortcomings in aesthetics and flexibility of existing crowns, and improves aesthetics and bonding strength of crowns, simplifies workflow and reduces costs.

CN119587186APending Publication Date: 2025-03-11SOLVENTUM INTELLECTUAL PROPERTIES CO
View PDF 26 Cites 0 Cited by

Patent Information

Application Number
CN202411776285.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-03-07
Filing Date
2017-02-22
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing preformed crowns have shortcomings in aesthetics and flexibility, especially the metal surface does not meet aesthetic requirements, and the material properties limit the complexity of concave design and adhesion technology.

Method used

A preformed composite crown is employed, made of chemical compositions containing nanofillers and resin matrix, with specific shape and mechanical properties, including thin-walled designs and concave structures for improved aesthetics and bond strength.

Benefits of technology

It achieves the aesthetics and bonding strength of the crown, simplifies workflow, and reduces production and use costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119587186A_ABST
    Figure CN119587186A_ABST
Patent Text Reader

Abstract

The present invention relates to a preformed composite crown characterized by its shape and chemical composition, the shape being characterized by having an occlusal top surface and depending buccal, mesial, distal and lingual side surfaces, which side surfaces are connected to one another and form a crown neck, the crown having a wall thickness of less than 0.6 mm at the crown neck; at least two of the oppositely depending side surfaces have a concave shape; the chemical composition of the material for preparing the preformed composite dental crown is a hardening composition comprising the following components; the present invention relates to a chemical composition comprising a resin matrix comprising a urethane (meth) acrylate and a (meth) acrylate not comprising a urethane moiety, a nanofiller in an amount of 20 to 70 wt%, and a resin matrix in an amount of 20 to 75 wt%, the wt% relative to the weight of the chemical composition, the resin matrix comprising a urethane (meth) acrylate and a (meth) acrylate not comprising a urethane moiety. The invention also relates to a kit of parts comprising such a preformed composite crown, to a method for producing such a crown and to the use of such a crown for treating teeth.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese invention patent application No. 201780015660.9, whose application date is February 22, 2017 and invention name is "Preformed composite crown, its production method and use". Technical Field

[0002] The present invention relates to hardened preformed composite crowns, kits of parts containing these crowns, methods of production and uses thereof. The preformed crowns are particularly useful for treating missing teeth in children. Background Art

[0003] For the treatment of dental diseases, a variety of different solutions are available on the market at the same time.

[0004] Generally speaking, dental disease can be treated with either restorative or prosthetic methods.

[0005] Prosthetic methods are often used if there is not enough remaining tooth structure left that allows for restorative treatment, such as by filling the cavity with a dental filling material.

[0006] Prosthetic treatment usually begins with taking dental impressions based on the condition of the teeth in the patient's mouth. The records obtained represent the current condition.

[0007] In a next step, the tooth to be treated is further prepared, ie the tooth is shaped into a form which later allows the fixing of an artificial crown.

[0008] Artificial crowns are usually designed based on information obtained from dental impressions and the shape of the treated tooth.

[0009] In the next step, an artificial crown is produced in a dental laboratory and is specially designed for this individual case. This process is time-consuming and expensive.

[0010] However, if a quick and inexpensive prosthetic treatment is desired, the practitioner may instead consider the use of a preformed crown. This treatment is often used in pediatric dentistry.

[0011] For this purpose, different prefabricated crown types are also available on the market.

[0012] The most common solution is stainless steel crowns (eg, from 3M Oral Care; 3M ESPE). Not only are stainless steel crowns affordable to manufacture, they are also durable.

[0013] Preformed crowns made of stainless steel have the additional benefit that they are pre-trimmed, bell-shaped and crimped for quick and easy placement. Stainless steel crowns easily hold and fit over the contours of the prepared tooth due to the so-called "snap-fit" feature.

[0014] However, due to their metallic surface, stainless steel crowns do not meet the desired aesthetic requirements.

[0015] To overcome this defect, a patch-type stainless steel crown has been proposed.

[0016] However, patch-type stainless steel crowns show only limited flexibility due to stiff walls at least in some areas of the crown. In addition, peeling of the patch of these crowns has been reported, and the metallic sheen of the underlying stainless steel crown detracts from the aesthetic appearance.

[0017] Therefore, it is recommended to try to make preformed crowns with other materials.

[0018] Zirconia ceramics (ZrO2) are quite common for individually designed crowns for aesthetic dentistry. ZrO2 has several unique material properties, such as extreme strength and toughness, translucency, dyeability and biocompatibility, which make it very suitable for crowns or even bridges. Therefore, it is not surprising that preformed zirconia crowns are also available on the market.

[0019] However, due to the material properties, the side walls of these crowns are not flexible and therefore an undercut design is not feasible. In addition, a different and more invasive tooth preparation is required compared to stainless steel crowns, without or with very limited possibilities for undercut retention, which again leads to more delicate cementation technology issues. Solutions that roughen the inner surface of the crown, such as sandblasting or surface retention structures should help support the cementation of the crown, but cannot replace the undercut feature overall.

[0020] It has also been proposed to manufacture preformed crowns from polymer materials.

[0021] In this regard, US 8,651,867 B2 (Zilberman) describes a dental crown configured to be easily installed in a patient's mouth as part of the treatment of deciduous teeth and permanent molars, the crown having a natural appearance and color of a vital tooth and consisting of a layer of thermoplastic material configured to define a tooth-shaped top surface and flexible side surfaces.

[0022] As suitable thermoplastic materials, polymers selected from the group consisting of polyacetals, polyacrylates, polymethacrylates (PMMA), polyaryletherketones (PAEK), polyetherketones (PEK), polyetheretherketones (PEEK), polyetherimides (PEI), polyethersulfones (PES) and polysulfones (PSU) are proposed.

[0023] US2004 / 0161726 A1 (Saito et al.) describes a coronal prosthesis having wear resistance and aesthetic properties, which comprises a polymer of a mixture of polymerizable compounds having unsaturated double bonds, a filler and a polymerization initiator, and has a tooth-like outer shape and a space between its inner surface and the abutment to be filled with a dental composite resin.

[0024] However, even with the use of a more flexible material, the workflow required to apply a preformed crown based on a polymer material is virtually no different than the workflow required to apply a preformed zirconia crown.

[0025] Commercially available polymer-based preformed crowns show wall thicknesses greater than 500 μm, which do not render them sufficiently flexible and therefore have no undercut design options as additional support for cementation.

[0026] The fact that the material properties do not allow thinner walls makes the walls the limiting factor in design choices.

[0027] However, to ensure adequate adhesive fixation of these crowns to the prepared tooth surface, even with the application of surface roughening, adhesive cementation is recommended or required, ideally with pre-treatment of the inner surface. This makes the entire prosthetic procedure more complicated and expensive. In general, for crowns and bridges, different cementation techniques are used.

[0028] These can be divided into several groups, such as temporary adhesives (e.g., RelyX from 3M Oral Care), TM TempNE / E; 3M ESPE), conventional cement (e.g., Ketac from 3M Oral Care TM CEM or Ketac TM CEM Plus; 3MESPE), self-adhesive resin cements (e.g., RelyX from 3M Oral Care TM Unicem; 3M ESPE) or adhesive resin cement (e.g., RelyX from 3M Oral Care TM Ultimate; 3M ESPE).

[0029] Generally speaking, cementation needs to last for the indicated service life, which can be achieved due to chemical bonding or mechanical retention or a combination thereof.

[0030] The choice of cement to be used or the general cementation technique for a particular indication is therefore influenced by the restorative material, the indication itself, the preparation technique, and cost and aesthetics also play a role.

[0031] For a fast and easy chairside workflow utilizing preformed crowns, such as in pediatric dentistry, a fast and easy cementation technique is not only desirable but also necessary.

[0032] For this reason, conventional cementation techniques are used to secure stainless steel crowns. These cements not only have an easier workflow, but are also cheaper than self-adhesive or adhesive resin cements. In addition, they are more resistant to moisture and less affected by blood and saliva than self-adhesive or adhesive cements.

[0033] This technique is the dominant technique in pediatric dentistry due to the time-saving chairside workflow and the fact that individually designed crowns are not necessarily required.

[0034] Finally, the widespread use of this type of crown is a result of its easy workflow in the dentist's chair. This easy workflow is very important for reducing chairside time.

[0035] An important factor in achieving this easy workflow is the availability of materials that enable an undercut design of the crown in the marginal area, which is possible due to the thin and therefore flexible side walls. Especially for primary molars, the undercut design leads to an easy, fast and low-invasive preparation technique for the tooth stump, which enables a so-called snap-fit ​​effect of the crown on the stump.

[0036] The snap-fit ​​effect also ensures easy placement of the crown. Furthermore, the undercut design and preparation technique results in a macro-mechanical retention of the crown that significantly supports cementation of the crown.

[0037] WO 2007 / 098485 A2 (Nusmile) describes a preformed dental crown having a central surface, a peripheral surface transitioning from and integrally formed with the central surface, wherein the peripheral surface includes a tapered portion toward the gingival end, and wherein the tapered portion has a thickness ranging from 0 to 0.5 mm at the gingival edge to at least 1.0 mm near the transition to the central surface.

[0038] WO 2008 / 033758 A2 (3M) describes a solid dental crown comprising a self-supporting solid hardenable preformed dental crown having an external crown shape defined by an external crown surface.

[0039] US2007 / 0196792 A1 (Johnson et al.) describes a prefabricated crown that is tooth-colored and has an undercut. The materials that can be used to make the prefabricated crown are said to be thermoplastic resins such as polyacetal, polyacrylate, polyamide, polyaryletherketone, polyetheretherketone (PEEK), polyetherimide, and the like.

[0040] However, none of the solutions proposed in the prior art are completely satisfactory.

[0041] All of these types of crowns have disadvantages in different aspects, primarily related to a more complex and time-consuming workflow, but also due to durability and / or aesthetics. Summary of the invention

[0042] It is therefore an object of the present invention to provide a preformed dental crown similar to preformed dental crowns made of stainless steel but having better aesthetics, which preformed dental crown can be easily and securely fixed on a prepared tooth.

[0043] Additionally, it would be desirable to accomplish the affixation of the crown to the prepared tooth with low labor and at low cost, such as by using products of the resin modified glass ionomer cement class.

[0044] At least one of the above mentioned objects may be solved by the preformed dental crown and the related methods of production and use thereof as described herein.

[0045] Thus, according to one aspect, the present invention relates to a preformed composite dental crown characterized by its shape and chemical composition,

[0046] - The shape is characterized as follows:

[0047] o For molars and premolars, they have an occlusal apical surface and overhanging buccal, mesial, distal and lingual, respectively palatal surfaces,

[0048] o For the anterior and incisor teeth, they have a distal top surface and overhanging labial, mesial, distal and lingual, respectively palatal surfaces,

[0049] ○The wall thickness of the crown at the crown neck is less than 0.6mm;

[0050] o at least two of the oppositely overhanging side surfaces have a concave shape;

[0051] - The chemical composition of the material from which the preformed composite crown is made is a hardening composition and is characterized by comprising the following components:

[0052] ○Nano filler: 20 to 70 wt %,

[0053] ○ Resin matrix: 20 to 75 wt %,

[0054] ○ The resin matrix comprises the polymerization product of:

[0055] ■ a urethane (meth)acrylate having at least 2 polymerizable moieties, and

[0056] ■ a (meth)acrylate having at least 1 or 2 polymerizable moieties but not comprising a urethane moiety,

[0057] Weight % is relative to the weight of the chemical composition.

[0058] According to another aspect, the present invention relates to a method of producing a preformed composite dental crown as described herein using any of the following techniques: additive manufacturing techniques, molding techniques, milling the preformed composite dental crown from a milling block.

[0059] The invention also relates to a kit of parts comprising a set of preformed dental crowns as described herein.

[0060] The preformed composite crowns described herein are particularly useful for treating pediatric dental disease.

[0061] In particular, the present invention relates to the following:

[0062] 1. A preformed composite dental crown characterized by its shape and chemical composition,

[0063] The shape is characterized as follows:

[0064] For molars and premolars, they have an occlusal top surface and overhanging buccal, mesial, distal and lingual, respectively palatal surfaces,

[0065] For the anterior teeth and incisors, it has a distal top surface and overhanging labial, mesial, distal and lingual, respectively palatal surfaces,

[0066] The side surfaces are connected to each other and form a crown neck,

[0067] The wall thickness of the crown at the crown neck is less than 0.6 mm;

[0068] at least two of the oppositely depending side surfaces have a concave shape;

[0069] The chemical composition of the material from which the preformed composite crown is made is a hardening composition comprising the following components:

[0070] an amount of 20% to 70% by weight of nanofillers,

[0071] an amount of 20% to 75% by weight of a resin matrix,

[0072] Weight % is relative to the weight of the chemical composition,

[0073] The resin matrix comprises a urethane (meth)acrylate and a (meth)acrylate that does not comprise a urethane moiety.

[0074] 2. The composite dental crown according to item 1, wherein the shape is further characterized by at least one, more or all of the following features:

[0075] The wall thickness of the side surface of the crown: no more than 0.6 mm;

[0076] The wall thickness of the side surface of the crown is 0.1 mm to 0.4 mm;

[0077] The wall thickness of the top surface of the crown is 0.15 mm to 1.5 mm;

[0078] Undercut: greater than 0.2mm.

[0079] 3. The composite dental crown according to any of the preceding items, wherein the nanofiller comprises particles of SiO2, ZrO2, Al2O3 or a mixture thereof.

[0080] 4. The composite dental crown according to any one of the preceding claims, wherein the nanofiller comprises aggregated, agglomerated, discrete nanoscale particles or a mixture thereof.

[0081] 5. The composite crown according to any of the preceding items, wherein the urethane (meth)acrylate is characterized as follows:

[0082] With structure A-(-S1-U-S2-MA) n ,in

[0083] A is a connecting element comprising at least one unit,

[0084] S1 is a spacer group comprising at least 4 units connected to each other,

[0085] S2 is a spacer group comprising at least 4 units connected to each other,

[0086] The units of A, S1 and S2 are independently selected from CH3-, -CH2-, -O-, -S-, -NR 1 -、-CO-、-CR 1 =、 -N=、-CR 1 R 2 -,

[0087] Where R 1 and R 2 independently selected from hydrogen, alkyl, substituted alkyl, alkenyl, cycloalkyl, substituted cycloalkyl, aralkyl, aryl or substituted aryl, wherein these units can form linear, branched or cyclic structures, such as alkyl, cycloalkyl, aryl, ester, carbamate or amide groups,

[0088] U is a carbamate group connecting the spacer groups S1 and S2,

[0089] MA is an acrylate or methacrylate group, and

[0090] n is 3 to 6.

[0091] 6. The composite dental crown according to any of the preceding items, wherein the (meth)acrylate not comprising a urethane moiety is characterized as follows:

[0092] The molecular weight ranges from 170 g / mol to 3,000 g / mol,

[0093] Contains at least 2 polymerizable moieties.

[0094] 7. The composite dental crown according to any of the preceding items, wherein the chemical composition of the composite dental crown does not contain any or all of the following components:

[0095] An amount of a polymerizable component (w) having an acidic group greater than 2% by weight;

[0096] Amounts greater than 5% by weight of solvent;

[0097] The weight % is relative to the weight of the composite crown.

[0098] 8. The composite crown according to any one of the preceding items, wherein the chemical composition used to make the composite crown comprises

[0099] an amount of 20 wt % to 70 wt % of a nanofiller selected from aggregated, agglomerated or discrete nanoparticles and mixtures thereof,

[0100] urethane (meth)acrylate in an amount of 3% to 20% by weight,

[0101] an amount of 5 to 55 wt. % of a (meth)acrylate not comprising a urethane moiety,

[0102] The weight % is relative to the weight of the chemical composition of the composite crown.

[0103] 9. The composite dental crown according to any of the preceding claims, wherein the chemical composition of the composite dental crown is characterized by any one or a combination of the following parameters:

[0104] Flexural strength: 50MPa to 200MPa or 80MPa to 150MPa determined according to ISO 4049:2009,

[0105] Modulus of elasticity: 1,000 MPa to 4,000 MPa determined according to ISO 4049:2009 in combination with DIN EN 843-2:2007;

[0106] Impact strength: 5 kJ / m determined according to DIN 53453:175-05 2 Up to 15kJ / m 2 ,

[0107] Wear: less than about 20mm 3 or less than 15mm 3 or less than 10mm 3 ,

[0108] Color: Tooth color.

[0109] 10. The composite dental crown according to any of the preceding items, characterized in that:

[0110] The shape is characterized as follows:

[0111] For molars and premolars, they have an occlusal top surface and overhanging buccal, mesial, distal and lingual, respectively palatal surfaces,

[0112] For the anterior teeth and incisors, it has a distal top surface and overhanging labial, mesial, distal and lingual, respectively palatal surfaces,

[0113] The side surfaces are connected to each other and form a crown neck,

[0114] The wall thickness of the crown at the crown neck is 0.1 mm to 0.4 mm,

[0115] The wall thickness of the top surface is 0.15 mm to 1.5 mm,

[0116] At least two of the oppositely overhanging side surfaces have a concave shape, resulting in an undercut design greater than 0.2 mm,

[0117] The chemical composition of the material from which the preformed composite crown is made is a hardening composition and is characterized by comprising the following components:

[0118] an amount of 20% to 70% by weight of nanofillers,

[0119] an amount of 20% to 75% by weight of a resin matrix,

[0120] The resin matrix comprises the polymerization product of

[0121] urethane (meth)acrylate having at least 2 polymerizable moieties in an amount of 3 to 20 weight percent, and

[0122] an amount of 5 to 55 wt. % of a (meth)acrylate having at least 2 polymerizable moieties but not comprising a urethane moiety,

[0123] Weight % is relative to the weight of the chemical composition,

[0124] The chemical composition is characterized by the following parameters:

[0125] Impact strength: 5 kJ / m determined according to DIN 53453:175-05 2 Up to 15kJ / m 2 ,

[0126] Modulus of elasticity: 1,000 MPa to 4,000 MPa determined according to ISO 4049:2009 in conjunction with DIN EN 843-2:2007.

[0127] 11. A kit of parts, comprising a set of preformed composite dental crowns according to any preceding claim, the preformed composite dental crowns being distinguishable from one another by any of the following: shape, colour, size or a combination thereof.

[0128] 12. The kit according to item 11, further comprising a dental cement and optionally a dental composite material.

[0129] 13. The kit according to item 11 or 12, wherein the dental cement is a resin-modified glass ionomer cement, a self-adhesive resin cement or an adhesive resin cement.

[0130] 14. A composite dental crown for use in a method for treating a tooth, the method comprising the step of fixing the composite dental crown according to any one of items 1 to 9 to a surface of a prepared tooth in a patient's mouth by using the dental adhesive according to item 12 or 13.

[0131] 15. A method of producing a preformed composite crown according to any one of items 1 to 10, the method being carried out by any one of the following methods:

[0132] Applying additive manufacturing technology,

[0133] Applying molding technology,

[0134] The preformed composite crown is ground from a grinding block. BRIEF DESCRIPTION OF THE DRAWINGS

[0135] Figure 1 An example of a preformed composite crown placed on a tooth model is shown.

[0136] Figure 2 It is illustrated how the undercut of a preformed composite crown may be determined.

[0137] Figure 3The shape of the preformed composite crown used to conduct the adhesive experiments is shown in cross section.

[0138] Figure 4 The shape of the prepared artificial tooth is shown in cross section.

[0139] Figure 5 A table with test results is shown. DETAILED DESCRIPTION

[0140] Unless otherwise defined, for the purposes of this specification, the following terms shall have the given meanings:

[0141] A "hardenable component or material" or "polymerizable component" is any component that can be cured or hardened, for example, by heating to cause polymerization, chemical crosslinking, radiation-induced polymerization, or by crosslinking using a redox initiator. A hardenable component may contain only one, two, three or more polymerizable groups. Typical examples of polymerizable groups include unsaturated carbon groups, such as vinyl groups, especially those present in (meth)acrylate groups.

[0142] An "initiator" is a substance that is capable of starting or initiating the curing process of a hardenable composition.

[0143] A "monomer" is any chemical species that can be characterized by a chemical formula and carries polymerizable groups (including (meth)acrylate groups) that can be polymerized into oligomers or polymers to increase molecular weight. The molecular weight of a monomer can usually be calculated simply based on a given chemical formula.

[0144] As used herein, "(meth)acryloyl" is an abbreviation that refers to "acryloyl" and / or "methacryloyl." For example, a "(meth)acryloyloxy" group is an abbreviation that refers to either an acryloxy group (i.e., CH2=CH-C(O)-O-) and / or a methacryloyloxy group (i.e., CH2=C(CH3)-C(O)-O-).

[0145] "Curing, hardening or setting reaction" are used interchangeably and refer to a reaction in which the physical properties of a composition, such as viscosity and hardness, change over time due to chemical reactions between the various components.

[0146] "Polymerizable components containing acidic groups" are intended to include monomers, oligomers and polymers having ethylenically unsaturated functional groups and acid functional groups and / or acid precursor functional groups. Acidic precursor functional groups include, for example, acid anhydrides, acid halides and pyrophosphates. The acidic groups preferably contain one or more carboxylic acid residues such as -COOH or -CO-O-CO-, phosphoric acid residues such as -OP(O)(OH)OH, phosphonic acid residues such as CP(O)(OH)OH, sulfonic acid residues such as -SO3H or sulfinic acid residues such as -SO2H.

[0147] "Powder" means a dry bulk solid consisting of a plurality of very fine particles which flow freely when vibrated or tilted.

[0148] "Particle" means a solid substance having a geometrically definable shape. Particles can be generally analyzed, for example, based on grain size or diameter.

[0149] The average particle size of the powder can be obtained from the cumulative curve of the grain size distribution and is defined as the arithmetic mean of the measured grain sizes of a certain powder mixture. The corresponding measurement can be completed using a commercially available particle size meter (e.g., CILAS laser diffraction particle size analyzer).

[0150] A "nanofiller" is a filler whose individual particles have a size in the nanometer region, for example an average particle size of less than about 200 nm, or less than about 100 nm, or less than about 50 nm. US 6,899,948 and US 6,572,693 give useful examples, particularly with respect to nano-sized silica particles, which are incorporated herein by reference.

[0151] The measurement of the size of the nanoparticles is preferably based on the TEM (transmission electron microscopy) method, whereby the population is analyzed to obtain the average particle size. The preferred method for measuring particle size can be described as follows:

[0152] Samples with a thickness of no more than 80 nm were placed on a 200 mesh copper grid with a carbon stabilized polyvinyl acetate substrate (SPI Supplies-a division of Structure Probe, Inc., West Chester, PA). Transmission electron micrographs (TEM) were taken at 200 KV using a JEOL 200CX (JEOL, Ltd. of Akishima, Japan, and sold by JEOL, USA). The population size of about 50-100 particles can be measured and the average diameter determined.

[0153] "Agglomerated" describes a weakly associated state of particles that are usually held together by charge or polarity and that can be broken down into smaller entities. The specific surface area of ​​the agglomerated particles does not deviate substantially from the specific surface area of ​​the primary particles from which the agglomerate is made (see DIN 53206; 1972).

[0154] The agglomerated fillers are available, for example, under the product name Aerosil TM 、CAB-O-SIL TM HDK and HDK are commercially available from Degussa, Cabot Corp, or Wacker.

[0155] "Non-agglomerated filler" means that the filler particles are present in the resin in discrete, non-associated (ie, non-agglomerated and non-aggregated) phases. This can be demonstrated by TEM microscopy if desired.

[0156] Non-agglomerated nano-sized silica is commercially available under the product designation NALCO COLLOIDAL SILICAS, such as NALCO products #1040, 1042, 1050, 1060, 2327, and 2329, for example, from Nalco Chemical Co. (Naperville, Ill.).

[0157] Non-agglomerated fillers are used and described, for example, in EP 2 167 013 B1 (3M). The content of this reference is incorporated herein by reference.

[0158] "Agglomerated" as used herein describes a strong association of particles that are often held together by, for example, residual chemical treatment or partial sintering. The specific surface area of ​​the aggregated particles is generally smaller than that of the primary particles from which the aggregates are made (see DIN 53206; 1972).

[0159] Further breakdown of the aggregates into smaller entities may occur during the step of applying a polishing step to the surface of the composition containing the aggregated filler, rather than during the dispersion of the aggregated particles in the resin.

[0160] Aggregate fillers and methods for their production and surface treatment are described, for example, in WO 01 / 30304 and US 6,730,156 (3M). The contents of these references are incorporated herein by reference. A "carbamate group" is a group having the structure "-NH-CO-O-".

[0161] "Additive manufacturing" means a process for making 3-dimensional articles. An example of an additive manufacturing technique is stereolithography (SLA), in which successive layers of material are laid down under computer control. The article can have almost any shape or geometry and is produced from a 3-dimensional model or other electronic data source. Other examples of additive manufacturing methods or techniques include 3d printing.

[0162] "Abrasive block" means a solid block of material (three-dimensional article) from which a dental article, a dental workpiece, a dental support structure or a dental restoration can or will be processed. A dental abrasive block can have a size of 20 mm to 30 mm in two dimensions, for example, can have a diameter within this range, and can have a certain length in the third dimension. Blocks for making a single crown can have a length of 15 mm to 30 mm, and blocks for making bridges can have a length of 40 mm to 80 mm. The typical size of a block for making a single crown has a diameter of about 24 mm and a length of about 19 mm. In addition, the typical size of a block for making a bridge has a diameter of about 24 mm and a length of about 58 mm. In addition to the dimensions mentioned above, a dental abrasive block can also have the shape of a cube, a cylinder or a cuboid. If more than one crown or bridge is to be made from one blank, a larger abrasive block may be advantageous. For these cases, the diameter or length of the cylindrical or cuboid shaped grinding block may be in the range of 100 to 200 mm, with the thickness being in the range of 10 to 30 mm.

[0163] "Resin-modified glass ionomer cement" means a hardenable dental material comprising an acid-reactive glass, a polyacid, water, a polymerizable component, and an initiator. Resin-modified glass ionomer cements undergo a dual curing reaction, a cement reaction based on the glass ionomer acid-base and a polymerization reaction of monomers typically based on (methacrylate) acrylates.

[0164] "Adhesive resin cement" means a hardenable dental material that cures by free radical polymerization of the polymerizable components (but not by a glass ionomer cement reaction). Adhesive resin cements require pretreatment of the hard tooth surface to achieve bonding. In contrast to resin-modified glass ionomer cements, adhesive resin cements do not contain added water.

[0165] A "self-adhesive resin cement" is an adhesive resin cement which additionally contains an acidic component and which therefore does not require pre-treatment of the hard tooth surface to achieve bonding.

[0166] In contrast to resin-modified glass ionomer cements, adhesive resin cements and self-adhesive resin cements generally cure only by polymerization.

[0167] "Environmental conditions" means the conditions to which the composition of the invention is usually subjected during storage and handling. The environmental conditions may be, for example, a pressure of 900 to 1100 mbar, a temperature of -10°C to 60°C and a relative humidity of 10% to 100%. In the laboratory, the environmental conditions are adjusted to about 23°C and about 1013 mbar. In the dental and orthodontic fields, the environmental conditions are reasonably understood to be a pressure of 950 to 1050 mbar, a temperature of 15°C to 40°C and a relative humidity of 20% to 80%.

[0168] As used herein, "a", "an", "the", "at least one", and "one or more" are used interchangeably. The terms "comprising" or "containing" and their variations do not have a limiting meaning when they appear in the specification and claims. The term "comprising" also includes the more limiting expressions "consisting essentially of" and "consisting of".

[0169] Also herein, the recitations of numerical ranges by endpoints include all numbers subsumed within that range (eg, 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc.).

[0170] Adding a plural form to a term means that the term shall include both the singular and the plural. For example, the term "additive" means one additive and multiple additives (eg, 2, 3, 4, etc.).

[0171] Unless otherwise indicated, all numbers expressing quantities of ingredients, measurements of physical properties such as described below, and so forth used in the specification and claims are to be understood as being modified in all instances by the term "about."

[0172] The preformed composite crowns described herein have several advantages.

[0173] Preformed composite crowns can be used in a chairside workflow. Since the crown is already provided in a ready-to-use shape, there is no need to produce the crown in a separate step in the dental laboratory. This not only saves time for the patient, but is also convenient for the practitioner.

[0174] Compared to preformed crowns made from stainless steel, the preformed composite crowns described herein are far more aesthetically pleasing without adversely affecting the overall workflow.

[0175] Compared to preformed dental crowns based on zirconia or thermoplastic materials (eg, PEEK), the shape of the preformed composite dental crowns described herein can be easily further adjusted by a practitioner, such as by cutting or grinding, if desired.

[0176] However, similar to preformed crowns made of stainless steel, the preformed composite crowns described herein also exhibit a so-called "snap-fit ​​effect." That is, the fit of the crown on the prepared tooth can be easily checked before the crown is finally fixed.

[0177] Additionally, due to their flexible nature, preformed composite crowns can also be easily secured to tooth structure that is not optimally prepared.

[0178] This "snap-on effect" is essentially due to a) providing the crown with at least two oppositely depending side surfaces having a concave shape, b) adjusting the wall thickness of the crown at the crown neck to less than 0.6 mm, and c) manufacturing the crown from a material containing a hardened resin matrix containing urethane (meth)acrylate.

[0179] A reduced wall thickness of the crown at the crown neck is beneficial as this provides the crown with sufficient flexibility and enables an aesthetically pleasing marginal fit.

[0180] The preformed composite crowns described herein also exhibit several favorable mechanical properties, like adequate bending strength, work of fracture, elastic modulus, and wear resistance.

[0181] Preformed composite crowns can be easily and reliably cemented to prepared tooth surfaces. As mentioned above, in particular in pediatric dentistry, the treatment of defective tooth structure must be rapid and affordable. The cost for cementing the crown must not exceed the cost of the crown itself.

[0182] Surprisingly, it was found that the bond strength could be further improved if a dental resin modified glass ionomer cement was used.

[0183] Without wishing to be bound by a particular theory, it is believed that the use of a cement containing a polymerizable component with reactive moieties having structures similar to those used to produce preformed composite crowns may be beneficial in improving adhesion.

[0184] The preformed composite crowns described herein may also be readily produced by milling out from a preformed composite block, by injection molding, or by using additive manufacturing techniques (eg, 3D printing).

[0185] In summary, the preformed composite crowns described herein provide excellent esthetics, durability, and ease of workflow during use similar to methods used for stainless steel crowns.

[0186] The preformed composite crowns described herein have a specific shape.

[0187] The shape is characterized as follows: the preformed crown has an apical surface and overhanging buccal, respectively labial, mesial, distal, lingual, respectively palatal surfaces.

[0188] The side surfaces are connected to each other and form a crown neck. The lower area of ​​the crown neck forms the crown rim or crown edge of the tooth.

[0189] The preformed crown has an outer surface and an inner surface. The inner surface is the surface to be attached to the prepared tooth.

[0190] The wall thickness of the preformed crown at the crown neck (at a distance of 1 mm from the crown edge) is lower than 0.6 mm, or in the range of 0.1 to 0.4 mm, or 0.1 to 0.3 mm, or 0.1 to 0.2 mm.

[0191] The wall thickness of the top surface (occlusal and / or distal) of the preformed crown is typically in the range of 0.15 mm to 1.5 mm or in the range of 0.4 mm to 1.0 mm.

[0192] At least two of the opposing and overhanging side surfaces of the preformed crown have a concave shape, preferably the buccal and lingual surfaces. That is, the side walls of the preformed crown have a curved shape and thus provide an undercut in the crown neck region.

[0193] If necessary, the size of the undercut U in mm can be calculated by the formula U=D2-D1, where D1 is the distance of the opposite inner side walls having the concave shape of the preformed crown measured 1 mm above the crown neck (if the preformed crown is cut in half), and where D2 is the maximum distance of the opposite inner side walls of the crown measured parallel to D1.

[0194] exist Figure 2 In FIG. 1 , the corresponding distances D1 and D2 of a crown design in cross section are illustrated. The preformed composite crown has x, y and z directions. The cross section is taken in the middle of the crown in the z direction. Distance D1 is measured 1 mm from each crown edge in the y direction. Distance D2 is measured parallel to distance D1 in a y-shifted manner. Distance D2 is the maximum distance of the crown in this cross section.

[0195] The undercut (U=d2-d1) of the preformed composite crowns described herein is typically greater than 0.2 mm or 0.3 mm or 0.4 mm. A typical range is 0.2 to 1.0 or 0.3 to 0.8 mm.

[0196] In one embodiment, the shape of the preformed crown is further characterized by any of the following features alone or in combination:

[0197] The wall thickness of the side surface of the crown is usually no greater than 0.6 mm or 0.5 mm or 0.4 mm.

[0198] According to one embodiment, the wall thickness of the side surface of the preformed crown is in the range of 0.1 mm to 0.4 mm.

[0199] According to one embodiment, the inner surface of the preformed composite crown is roughened and / or has retention elements. This feature can help to enhance the bonding of the crown to the surface of the prepared tooth.

[0200] According to one embodiment, the outer surface of the preformed composite crown is polished.

[0201] This shape has proven to be beneficial in allowing the preformed crown to be easily secured to the prepared tooth stump.

[0202] Due to the low wall thickness, the preformed crown is flexible enough to be placed on the prepared tooth stump even in the presence of undercuts.

[0203] If the thickness of the side wall of the preformed crown is too large, the preformed crown does not have sufficient elasticity. If the thickness of the side wall of the crown is too small, the preformed crown is not strong enough.

[0204] This is also helpful if the fit of a preformed crown must be tested before cementation and the preformed crown must be removed from the prepared tooth stump for the application of a corresponding dental cement.

[0205] Generally speaking, dentists usually want preformed composite crowns to be as thin as possible. However, depending on the chemical composition of the preformed composite crown, the durability of the crown, such as wear or even complete breakage, limits the thickness to an appropriate level. On the other hand, the flexibility of the wall will decrease as the wall thickness increases.

[0206] It has been found that the wall thickness as described herein provides the required flexibility to provide a preformed crown with the desired snap-fit ​​effect.

[0207] Figure 1 A perspective view of a preformed composite crown as described herein is shown in The preformed composite crown (molar) is placed on a tooth stump of an artificial dental arch.

[0208] exist Figure 3 , a schematic cross-section of an embodiment of a preformed composite crown as described herein is shown. The crown wall has a thickness of about 300 μm.

[0209] If desired, the preformed composite dental crowns described herein may be characterized by the mechanical properties of the hardened chemical composition from which the composite dental crown is formed.

[0210] Typically, a chemical composition can be characterized by one or more or all of the following parameters:

[0211] Flexural strength: 50 to 200 MPa or 80 to 150 MPa as determined in accordance with ISO 4049:2009;

[0212] ● Modulus of elasticity: 1,000 to 4,000 MPa determined according to ISO 4049:2009 in combination with DIN EN 843-2:2007;

[0213] ● Impact strength: 5 to 15 kJ / m determined according to DIN 53453:175-05 2 ;

[0214] ● Wear: less than 20 or less than 15 or less than 10mm 3 (determined as described in the Examples section);

[0215] ●Color: tooth color.

[0216] The following combination of features is often preferred: high impact strength combined with low wear.

[0217] Sufficient bending strength is beneficial because the material of the crown does not break easily.

[0218] A sufficiently low modulus of elasticity is advantageous, since the material of the crown has sufficient flexibility.

[0219] Sufficient impact strength is beneficial because the material of the crown has high toughness and can resist fracture.

[0220] Sufficient wear is beneficial because the crown is not worn away during chewing and maintains its anatomical shape.

[0221] The preformed composite crowns described herein are also characterized by their chemical composition. The chemical composition is not a hardenable chemical composition, but rather a hardened (ie, cured) chemical composition.

[0222] The chemical composition from which the preformed composite crown is made includes nanofillers.

[0223] The nanofiller may be selected from aggregated, agglomerated or discrete (ie, non-agglomerated, non-agglomerated) nanoscale particles or mixtures thereof.

[0224] The use of nanofillers has been found to be beneficial compared to other fillers as it allows the formulation of compositions with high filler loadings, resulting in better mechanical properties such as polish or wear and improved aesthetics.

[0225] According to one embodiment, the nanofiller comprises aggregated nanoscale particles.

[0226] Nanofillers comprising aggregated nanoscale particles can generally be characterized by at least one or all of the following features:

[0227] -Specific surface area: 30 to 400 or 60 to 300 or 80 to 250 m 2 / g,

[0228] - Particles comprising SiO2, ZrO2, Al2O3 and mixtures thereof.

[0229] If desired, the specific surface area can be determined according to Brunauer, Emmet and Teller (BET) by using an apparatus available from Quantachrome (Monosorb TM ) to determine.

[0230] If desired, the average particle size can be determined by light scattering using, for example, a Malvern Mastersizer 2000 apparatus available from Malvern Instruments.

[0231] Suitable nanofillers comprising aggregated nanoscale particles can be produced according to the method described, for example, in US 6,730,156 (Preparation Example A).

[0232] The available nanofillers containing aggregated nano-sized particles can be prepared by suitable sols and one or more oxygen-containing heavy metal compound solution precursors, which can be salts, sols, solutions or nano-sized particles; among these, sols are preferred. For the purposes of the present invention, sols are defined as stable dispersions of colloidal solid particles in a liquid. The solid particles are usually denser than the surrounding liquid and small enough so that the dispersion force is greater than gravity. In addition, the particles have a sufficiently small size so that they generally do not refract visible light. Judicious selection of the precursor sol results in a desired degree of visual opacity, strength, etc. Factors that will guide the choice of the sol depend on a combination of the following properties: a) the average size of the individual particles, which are preferably less than 100 nm in diameter; b) acidity: the pH of the sol should preferably be below 6, and more preferably below 4, and c) the sol should be free of impurities that would cause the individual discrete particles (during filler preparation) to undesirably aggregate into larger sized particles during subsequent steps such as spray drying or calcination, which cannot be easily dispersed or reciprocated and thus reduce the translucency and polishability of dental restorations made with composite materials containing such nanoparticles.

[0233] If the starting sol is alkaline, it should be acidified, for example by adding nitric acid or other suitable acid, to reduce the pH. However, the selection of an alkaline starting sol is less desirable because it requires additional steps and may result in the introduction of undesirable impurities. Typical impurities that are preferably avoided are metal salts, especially alkali metals, such as sodium salts.

[0234] The non-heavy metal sol and the heavy metal oxide precursor are preferably mixed together in a molar ratio that matches the refractive index of the hardenable resin. This imparts a low and desirable visual opacity. Preferably, the molar ratio of the non-heavy metal oxide ("non-HMO") to the heavy metal oxide ("HMO") expressed as non-HMO:HMO ranges from 0.5:1 to 10:1, more preferably from 3:1 to 9:1, and most preferably from 4:1 to 7:1.

[0235] In a preferred embodiment where the aggregated nanoparticles contain silica and a zirconium-containing compound, the preparation method begins with a mixture of silica sol and zirconyl acetate in a molar ratio of about 5.5:1.

[0236] Prior to mixing the non-heavy metal oxide sol with the heavy metal oxide precursor, the pH of the non-heavy metal oxide sol is preferably reduced to provide an acidic solution having a pH of 1.5 to 4.0.

[0237] The non-heavy metal oxide sol is then slowly mixed with a solution containing a heavy metal oxide precursor and stirred vigorously. Strong stirring is preferably performed throughout the blending process. The solution is then dried to remove water and other volatile components. Drying can be achieved in a variety of ways, including, for example, tray drying, fluidized bed, and spray drying. In a preferred method using zirconyl acetate, drying is performed by means of spray drying.

[0238] The resulting dried material is preferably composed of small substantially spherical particles, as well as broken hollow spheres. These fragments are then calcined in batches to further remove residual organic matter. The removal of residual organic matter makes the filler more brittle, which causes more effective particle size crushing. During the calcination process, the hot calcination temperature is set to preferably 200°C to 800°C, more preferably 300°C to 600°C. The hot calcination is carried out for 0.5 hours to 8 hours, depending on the amount of material being calcined. Preferably, the hot calcination time of the calcination step is such that a smooth surface area can be obtained. Preferably, the time and temperature are selected so that the resulting filler is white as determined by visual inspection, without black, gray or amber particles.

[0239] The calcined material is then preferably ground to a median particle size of less than 5 μm, preferably less than 2 μm (based on volume), as can be determined using a Sedigraph 5100 (Micrometrics, Norcross, Ga.). Particle size determination can be performed by first obtaining the specific density of the filler using an Accuracy 1330 Pycometer (Micrometrics, Norcross, Ga.). Grinding can be achieved by various methods, including, for example, stirred grinding, vibratory grinding, fluid energy grinding, jet grinding, and ball milling. Ball milling is a preferred method.

[0240] The resulting filler comprises, contains, consists essentially of, or consists of aggregated nanoscale particles. If desired, this can be demonstrated by transmission electron microscopy (TEM).

[0241] If necessary, the surface of the filler particles may be surface treated. The surface treatment may be achieved according to the method described in US 6,730,156 or WO 01 / 30304 or US 6,730,156 (e.g., Preparation Example B). The contents of these references are incorporated herein by reference.

[0242] Once dispersed in the resin, the filler remains in the aggregate stage. That is, during the dispersion step, the particles do not break down into discrete (ie, individual) and non-associated (ie, non-aggregated) particles.

[0243] If present, the nanofiller comprising aggregated nanoscale particles is typically present in any of the following amounts:

[0244] - at least 20% by weight or at least 30% by weight or at least 40% by weight relative to the weight of the chemical composition of the preformed composite crown.

[0245] - at most 70 wt.-% or at most 60 wt.-% or at most 50 wt.-% relative to the weight of the chemical composition of the preformed composite crown.

[0246] - 20% to 70% by weight or 30% to 60% by weight or 40% to 50% by weight relative to the weight of the chemical composition of the preformed composite crown.

[0247] According to one embodiment, the nanofiller comprises agglomerated nanoscale particles.

[0248] Nanofillers comprising agglomerated nanoscale particles are generally characterized by at least one or all of the following features:

[0249] - Specific surface area: (BET is based on Brunauer, Emmet and Teller): 30 to 400 or 50 to 300 or 70 to 250 m 2 / g;

[0250] - Particles comprising SiO2, ZrO2, Al2O3 and mixtures thereof.

[0251] If desired, the specific surface area can be determined as described above.

[0252] Suitable agglomerated nanoparticles include fumed silica, such as those sold under the trade name Aerosil TM , such as Aerosil TM OX-130, -150 and -200, Aerosil TM R8200 is sold as a product available from Degussa AG, Hanau, Germany; CAB-O-SIL is available from Cabot Corporation, Tuscola, Ill. TM M5 products; and HDK available from Wacker TM , such as HDK-H 2000, HDK H15, HDK H18, HDK H20 and HDK H30 products.

[0253] The surface of the filler particles can be treated with a resin compatible surface treatment agent. Particularly preferred surface treatment agents or surface modifiers include silane treatment agents that can polymerize with the resin. Preferred silane treatment agents include γ-methyl-acryloxypropyl trimethoxysilane, which can be commercially available from Witco OSi Specialties (Danbury, Conn.) under the trade name A-174, and γ-glycidyloxypropyl trimethoxysilane, which can be obtained from United Chemical Technologies (Bristol, Pa.) under the trade name G6720.

[0254] Alternatively, a combination of surface modifiers can be used, wherein at least one agent has a functional group that can copolymerize with the hardenable resin. For example, the polymeric group can be an ethylenically unsaturated functional group or a cyclic functional group that is easy to ring-opening polymerization. The ethylenically unsaturated polymeric group can be, for example, an acrylate or methacrylate or a vinyl group. The cyclic functional group that is easy to ring-opening polymerization generally contains heteroatoms, such as oxygen, sulphur or nitrogen, and is preferably a 3-ring containing oxygen, such as epoxide. Other surface modifiers that generally do not react with the hardenable resin can be included to enhance dispersibility or rheological properties. The example of this type of silane includes, for example, alkyl or aryl polyether, alkyl, cycloalkyl, hydroxyalkyl, aryl, hydroxyaryl or aminoalkyl functional silane.

[0255] If present, the nanofiller comprising agglomerated nanoscale particles is typically present in any of the following amounts:

[0256] - at least 1 wt. % or at least 3 wt. % or at least 5 wt. % relative to the weight of the chemical composition of the preformed composite crown;

[0257] - at most 20 wt.-% or at most 15 wt.-% or at most 10 wt.-% relative to the weight of the chemical composition of the preformed composite crown.

[0258] - 1 to 20% by weight or 3 to 15% by weight or 5 to 10% by weight relative to the weight of the chemical composition of the preformed composite crown.

[0259] According to one embodiment, the nanofiller comprises discrete nanoscale particles.

[0260] Discrete nanoscale particles that may be used are preferably substantially spherical and substantially non-porous.

[0261] Nanofillers comprising discrete nanoscale particles are generally characterized by at least one or all of the following features:

[0262] - Average particle size: less than 200 nm or less than 100 nm;

[0263] - Particles comprising SiO2, ZrO2 and mixtures thereof.

[0264] The preferred nano-sized silica can be found under the product name NALCO TM COLLOIDAL SILICAS is commercially available from Nalco Chemical Co. (Naperville, Ill.). For example, preferred silica particles can be prepared using NALCO TMProducts 1040, 1042, 1050, 1060, 2327 and 2329 were obtained.

[0265] If present, discrete nanoscale particles are typically present in any of the following amounts:

[0266] - at least 1 wt. % or at least 3 wt. % or at least 5 wt. % relative to the weight of the chemical composition of the preformed composite crown;

[0267] - at most 30 wt.-% or at most 25 wt.-% or at most 20 wt.-% relative to the weight of the chemical composition of the preformed composite crown.

[0268] - 1% to 30% by weight or 3% to 25% by weight or 5% to 20% by weight relative to the weight of the chemical composition of the preformed composite crown.

[0269] According to one embodiment, the chemical composition of the preformed composite crown comprises:

[0270] - an amount of 20% to 70% by weight of aggregated nanoscale particles,

[0271] - an amount of 1% to 20% by weight of agglomerated nanoscale particles,

[0272] - Discrete nanoscale particles in an amount of 1 to 30 wt. %.

[0273] The chemical composition of a preformed composite crown includes a resin.

[0274] The resin is the polymerization product of: a urethane (meth)acrylate having at least two polymerizable moieties; and a (meth)acrylate having at least one or two polymerizable moieties but not comprising a urethane moiety.

[0275] If a different chemical composition is chosen, the desired mechanical properties often cannot be achieved.

[0276] The chemical composition of the preformed composite dental crown comprises at least one urethane (meth)acrylate having at least two polymerizable (meth)acrylate moieties.

[0277] If desired, the chemical composition may contain at least two, three or four different kinds of urethane (meth)acrylates.

[0278] It has been found that the addition of urethane (meth)acrylates to the resin composition helps to improve certain mechanical properties of the cured resin composition, like elastic modulus and fracture resistance.

[0279] In particular, the urethane (meth)acrylates described herein have been found to be useful.

[0280] The molecular weight of the urethane (meth)acrylate is at least about 450, or at least about 800, or at least about 1,000 g / mol.

[0281] Useful ranges include 450 to 3,000 or 800 to 2,700 or 1,000 to 2,500 g / mol.

[0282] Molecules having a molecular weight above about 450 g / mol or above about 1,000 g / mol are generally less volatile than molecules having lower molecular weights and, therefore, can help provide a biocompatible composition.

[0283] Additionally, if the molecular weight is not high enough, the required work of fracture to harden the dental composition may not be achieved.

[0284] Urethane (meth)acrylates for use in the composition are typically obtained by reacting an NCO-terminated compound with a suitable monofunctional (meth)acrylate monomer such as hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, preferably hydroxyethyl methacrylate and hydroxypropyl methacrylate.

[0285] Urethane (meth)acrylates can be obtained by various methods known to the skilled person.

[0286] For example, a polyisocyanate and a polyol can be reacted to form an isocyanate-terminated urethane prepolymer, which is then reacted with a (meth)acrylate, such as 2-hydroxyethyl (meth)acrylate. These types of reactions can be performed at room temperature or higher, optionally in the presence of a catalyst, such as a tin catalyst, a tertiary amine, etc.

[0287] The polyisocyanate that can be used to form the isocyanate functional urethane prepolymer can be any organic isocyanate having at least two free isocyanate groups, including aliphatic, cycloaliphatic, aromatic and araliphatic isocyanates.

[0288] Any known polyisocyanate may be employed, such as alkyl and alkylene polyisocyanates, cycloalkyl and cycloalkylene polyisocyanates, and combinations such as alkylene and cycloalkylene polyisocyanates.

[0289] Preferably, diisocyanates of the formula X(NCO)2 are used, in which X represents an aliphatic hydrocarbon radical having 2 to 12 C atoms, a cycloaliphatic hydrocarbon radical having 5 to 18 C atoms, an aromatic hydrocarbon radical having 6 to 16 C atoms and / or an araliphatic hydrocarbon radical having 7 to 15 C atoms.

[0290] Examples of suitable polyisocyanates include 2,2,4-trimethylhexamethylene-1,6-diisocyanate, hexamethylene-1,6-diisocyanate (HDI), cyclohexyl-1,4-diisocyanate, 4,4'methylene-bis(cyclohexyl isocyanate), 1,1'-methylenebis(4-isocyanato)cyclohexane, isophorone diisocyanate, 4,4'-methylene diphenyl diisocyanate, 1,4-tetramethylene diisocyanate, m- and p-tetramethylxylene diisocyanate, 1,4-phenylene diisocyanate, 2,6- and 2,4-toluene diisocyanate, 1,5-naphthylene diisocyanate, 2,4' and 4,4'-diphenylmethane diisocyanate, and mixtures thereof.

[0291] It is also possible to use higher-functional polyisocyanates known from polyurethane chemistry or otherwise modified polyisocyanates, for example containing carbodiimide groups, allophanate groups, isocyanurate groups and / or biuret groups. Particularly preferred isocyanates are isophorone diisocyanate, 2,4,4-trimethyl-hexamethylene diisocyanate and higher-functional polyisocyanates having an isocyanurate structure.

[0292] The isocyanate terminated urethane compound is terminated with a (meth)acrylate to produce a urethane (meth)acrylate compound. Generally speaking, any (meth)acrylate type capping agent having a terminal hydroxyl group and also having an acrylic or methacrylic moiety can be employed, with methacrylic moieties being preferred.

[0293] Examples of suitable endcapping agents include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, glycerol di(meth)acrylate and / or trimethylolpropane di(meth)acrylate. Particularly preferred is 2-hydroxyethyl methacrylate (HEMA) and / or 2-hydroxyethyl acrylate (HEA).

[0294] The equivalent ratio of isocyanate groups to compounds reactive toward isocyanate groups is from 1.1:1 to 8:1, preferably from 1.5:1 to 4:1.

[0295] The stepwise polyaddition reaction of isocyanates can take place in the presence of catalysts known from polyurethane chemistry, for example organotin compounds such as dibutyltin dilaurate or amine catalysts such as diazabicyclo[2.2.2]octane. In addition, the synthesis can take place in the melt or in a suitable solvent which can be added before or during the preparation of the prepolymer. Suitable solvents are, for example, acetone, 2-butanone, tetrahydrofuran, dioxane, dimethylformamide, N-methyl-2-pyrrolidone (NMP), ethyl acetate, alkyl ethers of ethylene and propylene glycol, and aromatic hydrocarbons. The use of ethyl acetate as solvent is particularly preferred.

[0296] Suitable examples of urethane (meth)acrylates include 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-dioxy-dimethacrylate (e.g., Plex 666-1, ), 7,7,9-trimethyl-4,13-dioxo-5,12-diazahexadecane-1,16-dioxy-dimethacrylate (UDMA), carbamates (methacrylates) derived from 1,4 and 1,3-bis(1-isocyanato-1-methylethyl)benzene (for example, as described in EP 0 934 926 A1), and mixtures thereof.

[0297] According to one embodiment, the urethane (meth)acrylate is characterized as follows:

[0298] -With structure A-(-S1-U-S2-MA) n ,in

[0299] -A is a connecting element comprising at least one unit,

[0300] -S1 is a spacer group comprising at least 4 units connected to each other,

[0301] -S2 is a spacer group comprising at least 4 units connected to each other,

[0302] The units of -A, S1 and S2 are independently selected from CH3-, -CH2-, -O-, -S-, -NR 1 -、-CO-、-CR 1 =、 -N=、-CR 1 R 2 -,

[0303] Where R 1 and R 2 independently selected from hydrogen, alkyl, substituted alkyl, alkenyl, cycloalkyl, substituted cycloalkyl, aralkyl, aryl or substituted aryl, wherein these units can form linear, branched or cyclic structures, such as alkyl, cycloalkyl, aryl, ester, carbamate or amide groups,

[0304] -U is a carbamate group connecting the spacer groups S1 and S2,

[0305] -MA is an acrylate or methacrylate group, and

[0306] -n is from 3 to 6.

[0307] According to one embodiment, the urethane (meth)acrylate is represented by the structure

[0308] A-(-S1-U-S2-MA) n

[0309] in

[0310] -A is a linking element comprising at least about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20 units,

[0311] -S1 is a spacer group consisting of units linked to each other and comprising at least about 4, 5, 6, 7, 8, 9 or 10 units,

[0312] -S2 is a spacer group consisting of units linked to each other and comprising at least about 4, 5, 6, 7, 8, 9, 10, 12, 15, 20 or 25 units,

[0313] -U is a carbamate group connecting the spacer groups S1 and S2,

[0314] -MA is an acrylate or methacrylate group, and

[0315] -n is 3 to 6 or 4 to 6 or 5 to 6.

[0316] It may be preferred that A has a cyclic structure and comprises at least about 6 units.

[0317] It may further be preferred that S1 has a linear or branched structure and comprises at least about 4 or about 6 units.

[0318] It may further be preferred that S2 has a linear or branched structure and comprises at least about 6 or about 8 units.

[0319] Urethane (meth)acrylates may also be preferred, wherein A has a cyclic structure and contains at least about 6 units, and S1 has a linear structure and contains at least about 4 units, and S2 has a linear structure and contains at least about 8 units, and U is a urethane group.

[0320] Neither the atoms of the urethane group connecting S1 and S2 nor the atoms of the (meth)acryloyl group belong to the spacer group S1 or S2. Therefore, the atoms of the urethane group are not regarded as units of the spacer group S1 or S2.

[0321] The nature and structure of the linking element are not particularly limited. The linking element may contain saturated (no double bonds) or unsaturated (at least one or two double bonds) units, aromatic or heteroaromatic units (containing aromatic structures including N, O and S atoms).

[0322] Specific examples of the connecting element A having a ring structure include:

[0323]

[0324] Specific examples of connecting elements A having a non-cyclic but branched structure include:

[0325]

[0326]

[0327] The dashed line indicates the bonding to the spacer group S1.

[0328] The nature and structure of the spacer groups S1 or S2 are also not particularly limited.

[0329] The spacer group consists of units connected to each other. Typical units include: CH3-, -CH2-, -O-, -S-, -NR 1 -、-CO-、-CR 1 =、 -N=、-CR 1 R 2 -, where R 1 and R 2 are independently selected from hydrogen, alkyl, substituted alkyl, alkenyl, cycloalkyl, substituted cycloalkyl, aralkyl, aryl or substituted aryl.

[0330] These units may form linear, branched or cyclic structures such as alkyl, cycloalkyl, aryl, ester, carbamate or amide groups.

[0331] The structure of S1 may be the same as the structure of S2. However, in some embodiments, the structure of S1 is different from S2. In a particular embodiment, the number of units present in S1 is less than or equal to the number of units present in S2.

[0332] In a particular embodiment, S1 may have a saturated hydrocarbon structure.

[0333] In another specific embodiment, S2 may have a saturated hydrocarbon structure.

[0334] Typical examples of useful spacer groups for S1 include:

[0335]

[0336] Dashed lines indicate chemical bonding to group A or group U.

[0337] Typical examples of useful spacer groups for S2 include:

[0338]

[0339] The dashed line indicates the chemical bonding to the (meth)acrylate group or to the group U. The number of units to be counted according to the invention is given in brackets.

[0340] Specific examples of the hardenable component (A1) include

[0341]

[0342] Further suitable urethane (meth) acrylates are based on α,ω-terminated poly(meth)acrylatdiols (eg as described in EP 1 242 493 B1) or may be polyester, polyether, polybutadiene or polycarbonate urethane (meth) acrylates (eg as described in US Pat. No. 6,936,642 B2).

[0343] The urethane (meth)acrylate is typically present in an amount of at least 1 wt %, or at least 3 wt %, or at least 4.5 wt % relative to the weight of the preformed composite dental crown.

[0344] The urethane (meth)acrylate is typically present in an amount of up to 20 wt %, or up to 15 wt %, or up to 10 wt % relative to the weight of the preformed composite crown.

[0345] Thus, the urethane (meth)acrylate is typically present in an amount of 1 wt % to 20 wt %, or 3 wt % to 15 wt %, or 4.5 wt % to 10 wt %, relative to the weight of the preformed composite dental crown.

[0346] If the amount of urethane (meth)acrylate is too high, the resulting material may become too flexible and may not be able to maintain its anatomical shape.

[0347] If the amount of urethane (meth)acrylate is too low, the resulting material may become too brittle and the work to fracture and impact strength may be adversely affected.

[0348] The resin of the chemical composition further comprises a (meth)acrylate having at least 1 or 2 polymerizable moieties but not comprising a urethane moiety.

[0349] Thus, a (meth)acrylate differs from a urethane (meth)acrylate, for example, in functionality, chemical moiety, molecular weight, or a combination thereof.

[0350] If desired, the chemical composition may contain at least two, three or four different kinds of (meth)acrylates.

[0351] Adding a (meth)acrylate to the resin composition helps to further improve the mechanical properties of the resin composition in its curing stage, especially with respect to flexural strength or wear resistance.

[0352] The molecular weight of the (meth)acrylate is typically at least 170 or at least 200 or at least 300 g / mol.

[0353] The molecular weight of the (meth)acrylate is generally in the range of 170 to 3,000, or 200 to 2,500, or 300 to 2,000 g / mol.

[0354] The (meth)acrylate has a free radical active functional group, and includes monomers, oligomers, and polymers having two or more ethylenically unsaturated groups.

[0355] Such free radical polymerizable materials include di- or poly-acrylates and methacrylates such as glycerol diacrylate, glycerol triacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, 1,3-propylene glycol diacrylate, 1,3-propylene glycol dimethacrylate, trimethylolpropane triacrylate, 1,2,4-butanetriol trimethacrylate, 1,4-cyclohexanediol diacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, sorbitol hexaacrylate, bis[1-(2-acryloyloxy)]-p-ethoxyphenyldimethylmethane, bis[1-(3-acryloyloxy-2-hydroxy)]-p-propoxyphenyl-dimethylmethane; diacrylates and dimethacrylates of polyethylene glycol having a molecular weight of 200-500, copolymerizable mixtures of acrylated monomers such as those of U.S. Pat. No. 4,652,274, and copolymerizable mixtures of acrylated monomers such as those of U.S. Pat. No. 4,652,274. 4,642,126; and vinyl compounds such as diallyl phthalate, divinyl succinate, divinyl adipate, and divinyl phthalate.

[0356] Preferred ethylenically unsaturated monomers are methacrylates and acrylate monomers, such as di(meth)acrylates of propylene glycol, butanediol, hexanediol, octanediol, nonanediol, decanediol and eicosanediol, di(meth)acrylates of ethylene glycol, polyethylene glycol and polypropylene glycol, ethoxylated bisphenol A, for example di(meth)acrylate of 2,2'-bis(4-(meth)acryloyl-oxytetraethoxyphenyl)propane, and (meth)acrylamide. Monomers used may additionally be esters of [α]-cyanoacrylic acid, crotonic acid, cinnamic acid and sorbic acid.

[0357] It is also possible to use the methacrylates mentioned in EP 0 235 826, such as bis[3[4]-methacryloyl-oxymethyl-8(9)-tricyclo[5.2.1.02,6 Particularly suitable are 2,2-bis-4 (3-methacryloyloxy-2-hydroxypropoxy) phenylpropane (Bis-GMA), 2,2-bis-4 (3-methacryloyloxypropoxy) phenylpropane, triethylene glycol dimethacrylate (TEGDMA) and bishydroxymethyl tricyclo-(5.2.1.0 2,6 ) decane di(meth)-acrylate.

[0358] It has been found that the use of (meth)acrylates and more particularly the above components can be beneficial in providing a hardening composition with sufficient mechanical strength, as the hardening composition can act as a crosslinking agent useful for improving the mechanical properties of the cured dental composition.

[0359] The (meth)acrylate is typically present in an amount of at least about 5 wt %, or at least about 10 wt %, or at least about 15 wt %, relative to the weight of the entire composition.

[0360] The (meth)acrylate is typically present in an amount of up to about 60 wt %, or up to about 50 wt %, or up to about 45 wt %, relative to the weight of the preformed composite dental crown.

[0361] Thus, the (meth)acrylate is typically present in an amount of 5 to 60 wt %, or 10 to 50 wt %, or 15 to 45 wt %, relative to the weight of the entire composition.

[0362] The chemical composition of the preformed composite crown may also include one or more additives.

[0363] Adding x-ray visible particles to dental compositions is beneficial because it enables practitioners to better identify dental materials in a patient's mouth and differentiate between sound tooth structure and dental restorative materials.Dental materials are radiopaque.

[0364] Radiopacity of dental materials is advantageous in certain situations where x-rays are used to diagnose dental conditions. For example, a radiopaque material will allow detection of secondary caries that may have formed in tooth tissue around a filling. The desired degree of radiopacity may vary, depending on the specific application and the practitioner's desire to evaluate the x-ray film.

[0365] Suitable x-ray visible particles include particles of metal oxides and metal fluorides. Oxides or fluorides of heavy metals with an atomic number greater than about 28 may be preferred. Heavy metal oxides or fluorides should be selected so as not to impart undesirable color or shade to the hardened resin where they are dispersed. For example, iron and cobalt can be disadvantageous because they impart dark and contrasting colors to the neutral tooth color of dental materials. More preferably, heavy metal oxides or fluorides are oxides or fluorides of metals with an atomic number greater than 30. Suitable metal oxides are oxides of yttrium, strontium, barium, zirconium, hafnium, niobium, tantalum, tungsten, bismuth, molybdenum, tin, zinc, lanthanides (i.e., elements with an atomic number ranging from 57 to 71, including end values), cerium and and combinations thereof. Suitable metal fluorides are, for example, yttrium trifluoride and ytterbium trifluoride. Most preferably, oxides and fluorides of heavy metals with an atomic number greater than 30 but less than 72 are optionally included in the material of the present invention. Particularly preferred radiopaque metal oxides include lanthanum oxide, zirconium oxide, yttrium oxide, ytterbium oxide, barium oxide, strontium oxide, cerium oxide, and combinations thereof. Other suitable fillers for increasing radiopacity are salts of barium and strontium, especially strontium sulfate and barium sulfate.

[0366] The heavy metal oxide or metal fluoride particles may be surface treated.

[0367] If present, the x-ray visible particles are typically present in an amount of 0.1 wt % to 15 wt %, or 1 wt % to 10 wt %, or 2 wt % to 5 wt %, relative to the weight of the total composition.

[0368] Other additives that may optionally be added include antimicrobial agents, pigments, dyes, stabilizers, and fluoride release materials.

[0369] Examples of pigments and dyes that can be used include titanium dioxide or zinc sulfide (lithopone), red iron oxide 3395, Bayferrox 920Z yellow, Neazopon blue 807 (a dye based on copper phthalocyanine) or Fast Yellow ER. These additives can be used for the sole coloring of the dental composition.

[0370] Examples of fluoride release agents that may be present include naturally occurring or synthetic fluoride minerals. These fluoride sources may optionally be treated with a surface treatment agent.

[0371] Other additives that may be added include stabilizers, especially free radical scavengers, such as substituted and / or unsubstituted hydroxyaromatic compounds (e.g., butylated hydroxytoluene (BHT), hydroquinone, hydroquinone monomethyl ether (MEHQ), 3,5-di-tert-butyl-4-hydroxyanisole (2,6-di-tert-butyl-4-ethoxyphenol), 2,6-di-tert-butyl-4-(dimethylamino)-methylphenol or 2,5-di-tert-butyl-hydroquinone, 2-(2'-hydroxy-5'- methylphenyl)-2H-benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)-2H-benzotriazole, 2-hydroxy-4-methoxy-benzophenone (UV-9), 2-(2'-hydroxy-4',6'-di-tert-pentylphenyl)-2H-benzotriazole, 2-hydroxy-4-n-octyloxybenzophenone, 2-(2'-hydroxy-5'-methacryloyl-oxy-ethylphenyl)-2H-benzotriazole, phenothiazine and HALS (hindered amine light stabilizer).

[0372] The presence of these additives is not absolutely necessary, and thus additives may be completely absent. However, if they are present, they are generally present in amounts that are not detrimental to the intended purpose.

[0373] Useful amounts of additives include:

[0374] ● at least about 0.1 wt % or at least about 0.5 wt % or at least about 1 wt % and / or

[0375] • Up to about 15 wt % or up to about 10 wt % or up to about 5 wt %.

[0376] Typical ranges include 0.1 wt % to 15 wt % or 0.5 wt % to 10 wt % or 1 wt % to 5 wt %.

[0377] According to one embodiment, the chemical composition of the preformed composite crown is described as follows:

[0378] -Nanofillers: 20 to 70% by weight,

[0379] - Urethane (meth)acrylate: 3 to 20 wt %,

[0380] - (Meth)acrylates not comprising urethane moieties: 5 to 60 wt %.

[0381] According to another embodiment, the chemical composition of the preformed composite crown is described as follows:

[0382] -Nanofillers: 30 to 55 wt%,

[0383] - Urethane (meth)acrylate: 5 to 15 wt %,

[0384] - (Meth)acrylates not comprising urethane moieties: 10 to 50% by weight.

[0385] According to one embodiment, the present invention also relates to a composite dental crown as described herein, which has a specific shape and is composed of a specific chemical composition:

[0386] The shape is characterized as follows:

[0387] For molars and premolars, they have an occlusal top surface and overhanging buccal, mesial, distal and lingual, respectively palatal surfaces,

[0388] For the anterior teeth and incisors, it has a distal top surface and overhanging labial, mesial, distal and lingual, respectively palatal surfaces,

[0389] The side surfaces are connected to each other and form a crown neck,

[0390] The wall thickness of the crown at the crown neck is 0.1 to 0.4 mm, or 0.1 to 0.3 mm, and the wall thickness of the top surface is 0.15 mm to 1.5 mm.

[0391] At least two of the oppositely overhanging side surfaces have a concave shape, resulting in an undercut design of greater than 0.2 mm or greater than 0.3 mm,

[0392] The chemical composition of the material from which the preformed composite crown is made is a hardening composition and is characterized by comprising the following components:

[0393] an amount of 20 wt % to 60 wt % of nanofiller,

[0394] an amount of 20% to 75% by weight of a resin matrix,

[0395] The resin matrix comprises the polymerization product of:

[0396] urethane (meth)acrylate having at least 2 polymerizable moieties in an amount of 3 wt % to 20 wt %; and

[0397] an amount of 5 to 55 wt. % of a (meth)acrylate having at least 2 polymerizable moieties but not comprising a urethane moiety,

[0398] Weight % is relative to the weight of the chemical composition.

[0399] The chemical composition of the hardener is characterized by the following parameters:

[0400] Impact strength: 5 to 15 kJ / m determined according to DIN 53453:175-05 2, Modulus of elasticity: 1,000 to 4,000 MPa determined according to ISO 4049:2009 in combination with DIN EN 843-2:2007.

[0401] The chemical compositions described herein generally do not contain components selected from:

[0402] o For example, an amount greater than about 5% by weight of a polymerizable component containing acidic groups,

[0403] o For example, an amount greater than about 5% by weight of solvent,

[0404] o filler particles having an average particle size of 1 to 100 μm, for example in an amount greater than about 10% by weight or greater than about 5% by weight,

[0405] and mixtures thereof; weight % is relative to the weight of the preformed composite crown.

[0406] That is, those components are generally not added arbitrarily, and therefore are not present in amounts greater than about 10 wt %, or greater than about 8 wt %, or greater than about 5 wt %, or greater than about 2 wt %, relative to the weight of the entire composition.

[0407] However, depending on the raw materials selected, it may sometimes be unavoidable that the composition may contain trace amounts of any of the above components.

[0408] Adding a filler having an average particle size within the above-mentioned range in an amount above about 10 wt % may adversely affect properties like polishability and gloss retention.

[0409] Examples of such fillers include aluminofluorosilicate glass, quartz, frosted glass, water-insoluble fluorides such as CaF2, cristobalite, calcium silicate, zeolites including molecular sieves, metal oxide powders such as aluminum or zirconium oxide or mixed oxides thereof, barium sulfate, calcium carbonate.

[0410] The addition of such fillers in large amounts may adversely affect the aesthetic properties of the hardened dental composition.

[0411] Examples of solvents that are generally absent include linear, branched or cyclic, saturated or unsaturated alcohols, ketones, esters or mixtures of two or more of said types of solvents having 2 to 10 C atoms, like methanol, ethanol, isopropanol, n-propanol, THF, acetone, methyl ethyl ketone, cyclohexanol, toluene, alkanes and alkyl acetates.

[0412] All components used in the chemical compositions described herein should be sufficiently biocompatible, ie, the chemical compositions should not produce toxic, damaging, or immune responses in living tissue.

[0413] The preformed composite crowns described herein can be obtained by using different production techniques including additive manufacturing, molding and milling processes.

[0414] In all these cases, a hardenable composition is used which contains:

[0415] - a nanofiller as described herein,

[0416] - a urethane (meth)acrylate as described herein having at least 2 polymerizable moieties,

[0417] - a polymerizable (meth)acrylate as described herein which does not contain a urethane moiety,

[0418] - initiator systems suitable for curing urethane (meth)acrylates and (meth)acrylates,

[0419] -optionally additives as described herein.

[0420] Initiator systems that can be used to cure the chemical compositions described herein for preformed composite crowns are not particularly limited, but are typically triggered by radiation, heat, a combination of an oxidizing agent and a reducing agent (often referred to as a redox cure initiator system), or a combination thereof.

[0421] The initiator system can be a one-component system (eg, an initiator triggered by radiation or heat) or a two-component system (eg, a combination of an oxidizing agent and a reducing agent).

[0422] One class of initiators capable of initiating polymerization of free radically active functional groups includes conventional chemical initiator systems, such as combinations of organic peroxides and amines. These redox-reliant initiators are often referred to as "self-curing catalysts." They are typically supplied as two-part systems, where the reactants (reducing agent and oxidizing agent) are stored separately from one another and then mixed just before use.

[0423] Organic peroxide compounds together with so-called activators are also suitable as redox initiator systems. In particular, compounds such as lauroyl peroxide, benzoyl peroxide and p-chlorobenzoyl peroxide and p-toluyl peroxide can be regarded as organic peroxide compounds.

[0424] Suitable activators are, for example, tertiary aromatic amines such as N,N-bis-(hydroxyalkyl)-3,5-dimethylaniline and N,N-bis-(hydroxyalkyl)-3,5-di-tert-butylaniline known from US Pat. No. 3,541,068, in particular N,N-bis-([β]-oxybutyl)-3,5-di-tert-butylaniline and N,N-bis-(hydroxyalkyl)-3,4,5-trimethylaniline.

[0425] Very suitable activators are also barbituric acid and barbituric acid derivatives as described in US 2003 / 008967, DE 14 95 520 and malonylsulfonamides as described in US 4,544,742 (corresponding to EP 0 059451). Preferred malonylsulfonamides are 2,6-dimethyl-4-isobutylmalonylsulfonamide, 2,6-diisobutyl-4-propylmalonylsulfonamide, 2,6-dibutyl-4-propylmalonylsulfonamide, 2,6-dimethyl-4-ethylmalonylsulfonamide and 2,6-dioctyl-4-isobutylmalonylsulfonamide.

[0426] For further acceleration, the polymerization is preferably carried out in the presence of a heavy metal compound and an ionized halogen or pseudohalogen.

[0427] Heavy metals are suitable for use in the form of soluble organic compounds. Similarly, halogen ions and pseudohalogen ions are suitable for use in the form of soluble salts, which can be named as soluble amine hydrochlorides and quaternary ammonium chloride compounds as examples. Suitable accelerators are specifically metals, from iron to copper groups, preferably copper and iron complexes and especially copper complexes. Heavy metals are preferably used in the form of soluble organic compounds. Suitable are, for example, iron carboxylates, copper carboxylates, iron proteinates, copper proteinates, copper naphthenates, copper acetate and iron naphthenates.

[0428] For shelf life reasons, the oxidizing agent and reducing agent of redox cure initiator systems are usually stored separately.

[0429] According to one embodiment, the chemical composition of the preformed composite dental crown is cured by a lightless redox cure initiator system.

[0430] According to another embodiment, the chemical composition of the preformed composite dental crown is cured by a photocuring initiator system.

[0431] Such initiators may generally be capable of generating free radicals for polymerization when exposed to light energy having a wavelength between 400 and 800 nm.

[0432] Examples of visible light curing initiator components include, for example, systems based on amines and α-diketones. Suitable systems are described, for example, in US 4,071,124 and WO 2009151957. The contents of these references are incorporated herein by reference.

[0433] Alternatively, free radical initiators that may be used include acylphosphine oxides, such as described in US 4,737,593. Such acylphosphine oxides have the following general formula:

[0434] (R 9 )2—P(=O)—C(=O)—R 10

[0435] Each R 9 R may be independently a hydrocarbon group such as an alkyl group, a cycloalkyl group, an aryl group and an aralkyl group, any of which may be substituted by a halogen, an alkyl group or an alkoxy group, or both R 9 The group may be joined together with the phosphorus atom to form a ring, and wherein R 10 is a hydrocarbon group, a five-membered or six-membered heterocyclic group containing S-, O-, or N-, or -ZC(=O)-P(=O)-(R 9 )2 group, wherein Z represents a divalent hydrocarbon group such as an alkylene group or a phenylene group having 2 to 6 carbon atoms.

[0436] Preferred acylphosphine oxides are those in which R 9 and R 10 The acylphosphine oxide is bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (IRGACURE TM 819, Ciba Specialty Chemicals, Tarrytown, NY).

[0437] Tertiary amine reducing agents may be used in combination with the acylphosphine oxides. Exemplary tertiary amines include ethyl 4-(N,N-dimethylamino)benzoate and N,N-dimethylaminoethyl methacrylate.

[0438] Commercially available phosphine oxide photoinitiators capable of free radical initiation when irradiated at wavelengths greater than 400 nm to 1200 nm include a 25:75 by weight mixture of bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide and 2-hydroxy-2-methyl-1-phenylpropan-1-one (IRGACURE TM 1700, Ciba Specialty Chemicals), 2-benzyl-2-(N,N-dimethylamino)-1-(4-morpholinophenyl)-1-butanone (IRGACURE TM 369, Ciba Specialty Chemicals), bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl)titanium (IRGACURE TM 784DC, Ciba Specialty Chemicals), a 1:1 mixture by weight of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2-hydroxy-2-methyl-1-phenylpropan-1-one (DAROCUR TM4265, Ciba Specialty Chemicals), and ethyl-2,4,6-trimethylbenzylphenylphosphinate (LUCIRIN TM LR8893X, BASF Corp., Charlotte, NC).

[0439] According to another embodiment, the chemical composition of the preformed composite dental crown is cured by a combination of a redox initiator system and a photocurable initiator system.

[0440] In another alternative, heat can be used to initiate the hardening or polymerization of free radical reactive groups. Examples of heat sources suitable for use in the curable resin compositions described herein include induction, convection, and radiation. The heat source should be capable of generating a temperature of at least 40° C. to 150° C. under normal conditions. This procedure is preferred for initiating polymerization of materials outside of the oral environment. Suitable initiators that can be used and are sensitive to heat are, for example, organic peroxides.

[0441] According to one embodiment, the preformed composite crown is produced by applying additive manufacturing techniques.

[0442] For this technique it has been found useful to use an initiator system which is triggered by radiation.

[0443] A preformed composite crown may be obtained by a method comprising the following steps:

[0444] - providing a curable chemical composition comprising the components of the chemical composition of the preformed composite crown; and an initiator system suitable for curing the curable chemical composition - as described herein,

[0445] -Processing of curable chemical compositions into building materials in additive manufacturing processes.

[0446] Examples of this technology are further described in US 8,003,040 B2 (El-Siblani) which relates to a method for producing 3-dimensional articles by solidifying layers in a pattern using synergistically stimulating electromagnetic radiation. The contents of these references are incorporated herein by reference.

[0447] Using additive manufacturing techniques to produce pre-formed composite crowns may be useful if small or large quantities of pre-formed composite crowns having different shapes need to be produced.

[0448] According to one embodiment, the preformed composite crown is produced by applying a molding technique.

[0449] For this technique a wide variety of initiator systems can be used.

[0450] A preformed composite crown may be obtained by a method comprising the following steps:

[0451] - providing a curable chemical composition comprising the components of the chemical composition of the preformed composite crown; and an initiator system suitable for curing the curable chemical composition - as described herein,

[0452] - molding the curable chemical composition into a mold having the shape of the preformed crown to be produced,

[0453] - Curing the chemical composition to obtain a cured preformed composite crown.

[0454] Curing of the curable chemical composition may be initiated by application of heat, radiation, use of a redox cure system, or a combination thereof.

[0455] If large quantities of preformed and standardized composite crowns need to be produced, then using molding techniques to produce preformed composite crowns may be useful.

[0456] According to another embodiment, the preformed composite crown is produced by applying a milling technique.

[0457] For this technique, a wide variety of initiator systems can also be used.

[0458] A preformed composite crown may be obtained by a method comprising the following steps:

[0459] - providing a composite abrasive block having a chemical composition as described herein,

[0460] - Grinding out an article from the composite grinding block, the article having the shape of a preformed composite dental crown as described herein.

[0461] Composite abrasive segments can be manufactured using the molding techniques described above.

[0462] The use of milling techniques to produce preformed composite crowns may be useful if only a small number of preformed composite crowns need to be produced, or if production should be completed "chairside" near the dental practitioner during the course of treatment for the patient.

[0463] However, the use of grinding techniques is not always recommended, in particular due to geometrical limitations of the shape of the desired article (eg large undercuts).

[0464] The present invention also relates to a kit of parts comprising a set of preformed composite crowns as described herein.

[0465] Preformed composite crowns are typically differentiated from one another by any of the following: shape, color, size, or a combination thereof.

[0466] The kit may include up to 10 or up to 8 pre-formed composite crowns of different shapes.

[0467] The kit may include a quantity of up to 10 or up to 8 of each of the preformed composite crowns of different shapes of different sizes.

[0468] Thus, a kit may include up to 100 pre-formed composite crowns.

[0469] Preformed composite crowns can be in the shape of front or back teeth or molars.

[0470] Typically, preformed composite crowns are available in different tooth colors. Tooth color is usually based on Vita TM Color code to classify.

[0471] The kit of parts may also include a dental cement suitable for securely securing the preformed composite crown to the prepared tooth surface.

[0472] Suitable dental cements are glass ionomer cements and especially resin modified glass ionomer cements.Glass ionomer cements generally contain the following components: an acid reactive filler, a polyacid, water and a complexing agent, but no radiation curable component.

[0473] Glass ionomer cements are usually provided as a kit of parts including a liquid part and a powder part. The two parts must be mixed before use.

[0474] The powder portion typically contains an acid-reactive inorganic filler (eg, aluminofluorosilicate glass, FAS glass).

[0475] The liquid portion typically comprises a polyacid, water, and a complexing agent (eg, tartaric acid).

[0476] Glass ionomer cements are commercially available (e.g., Ketac TM Cem; 3M Oral Care; 3M ESPE).

[0477] Glass ionomer cement may also be provided as a kit of parts comprising two pastes A and B to be mixed prior to use.

[0478] According to a preferred embodiment, the kit of parts containing a preformed composite crown includes a resin modified glass ionomer cement (RM-GIZ).

[0479] Resin-modified glass ionomer cements generally contain the following components: acid-reactive filler, polyacid, water, complexing agent, radiation-curable component, initiator.

[0480] Suitable radiation curable components typically contain (meth)acrylate moieties.

[0481] Resin-modified glass ionomer cements are also provided as a kit of parts, either as a powder / liquid system or a paste / paste system.

[0482] The powder portion typically includes an acid-reactive inorganic filler (eg, aluminofluorosilicate glass, FAS glass) and an initiator component.

[0483] The liquid portion generally comprises a polyacid, water, a (meth)acrylate, and an initiator component.

[0484] Resin-modified glass ionomer cements are commercially available (e.g., Ketac TM Cem Plus; 3M OralCare; 3M ESPE).

[0485] Surprisingly, it has been found that RM-GIZ is particularly suitable for securely securing a preformed composite crown to the surface of a prepared tooth.

[0486] Although slightly more expensive than classic glass ionomer cements, they are comparable to self-adhesive resin cements (e.g., RelyX TM Unicem) or adhesive resin cements (e.g., RelyX TM Compared with the Ultimate, you can get RM-GIZ at a lower cost.

[0487] The preformed composite crowns described herein are used to treat teeth, particularly in the pediatric setting.

[0488] This method comprises the steps of securing a preformed composite dental crown as described herein to a surface of a prepared tooth in a patient's mouth by using a dental cement as described herein, particularly a resin-modified glass ionomer cement.

[0489] If desired, the surface of the preformed composite crown that is to be attached to the surface of the prepared tooth (the "inner surface") may be roughened prior to application of the dental cement. Roughening may be accomplished, for example, by sandblasting.

[0490] Roughening the surface may be used to even further improve the fixation of the preformed crown to the prepared tooth surface to be treated.

[0491] If necessary, the shape of the preformed composite crown can be further adjusted by cutting or grinding.

[0492] The entire disclosures of the patents, patent documents, and publications cited herein are incorporated by reference in their entirety, as if each individual document were individually incorporated by reference.

[0493] The following examples are given to illustrate the present invention.

[0494] Example

[0495] Unless otherwise indicated, all parts and percentages are by weight, all water is deionized water, and all molecular weights are weight average molecular weight. In addition, unless otherwise indicated, all experiments were performed under ambient conditions.

[0496] Measurement method

[0497] Bending Strength

[0498] If necessary, the flexural strength can be determined by carrying out a three-point flexural strength test according to ISO 4049: 2009 using a test specimen having a size of 2*2*25 mm. The flexural strength is given in [MPa].

[0499] Elastic modulus

[0500] If necessary, the elastic modulus can be determined with a bending strength measurement according to ISO 4049:2009 in combination with DIN EN 843-2:2007 using a test specimen having a size of 2*2*25 mm. The elastic modulus is determined to be between 20% and 50% of the maximum force of the test specimen. The elastic modulus is given in [GPa].

[0501] Impact strength

[0502] If necessary, the impact strength can be determined according to DIN 53453:1975-05 (Charpy) using a Zwick 5102 pendulum set to 0.5 J pendulum and using a 42 mm span, using test specimens with dimensions 4*6*50 mm. The impact strength is given in [kJ / m2].

[0503] Wear

[0504] If necessary, the wear [mm] can be determined as follows 3 ]: Wear tests were performed on specific samples at a slope of 30°. For this purpose, the material was filled into the recess of an M12 Inbus screw and cured according to the manufacturer's instructions.

[0505] The samples were flat ground using a 75 μm diamond saw and stored in distilled water at 36° C. for 4 days. The chewing simulation was then initiated applying the following conditions:

[0506] Chewing force: 80N; lateral movement: 4mm; sliding movement: 10mm; antagonist: talc ball; number of chewing cycles: 1,200,000; thermal cycle (5 / 55℃): 5,000.

[0507] After the chewing simulation was performed, abrasion was determined by measuring the volume loss using a laser scanning microscope VK-X200 (Keyence Company).

[0508] Further information on wear tests can be found in M. Rosentritt et al., Materialprüfung 39 (1997), pp. 77-80.

[0509] Crown Design :

[0510] A new preformed composite crown was designed using a 3M ESPE 3M Oral Care molar stainless steel crown (Type: ELR-3 / #N704922). The wall thickness of the stainless steel crown was essentially uniform (approximately 150 μm).

[0511] Using a dental scanner (Lava TM The inner surface of the stainless steel crown was scanned using Scan ST 2 and the wall thickness was uniformly scaled up to about 300 μm towards the outside using CAD software (3-matic, Base 6.0-software, build 6.0.0.13, Fa. Materialize NV). The inner surface of the crown design remained unchanged to ensure the same fit to the tooth stump.

[0512] By using CAM software (Lava TM The design software 7 (Configuration C), Version: 3.2.1.256-14 / 06 / 18) calculates the grinding strategy to prepare the crown design for grinding.

[0513] Figure 3 The design of the test crown is shown in .

[0514] Grinding block preparation

[0515] Chemical composition

[0516] The following components were provided and mixed using a mixer to obtain Paste A and Paste B.

[0517] Recipe (I)

[0518]

[0519]

[0520] Formula (III)

[0521]

[0522] Formula (IV)

[0523]

[0524]

[0525] abbreviation :

[0526]

[0527] The pastes were filled into double chamber cartridges (Sulzer Mixpac) in a volume ratio of paste A to paste B of 10:1.

[0528] Preparation of grinding blocks (I), (III) and (IV)

[0529] The corresponding composition was dispensed into a block mold (size: 18 mm*14 mm*12 mm) made of silicon material (Fa. Siladent, blau9:1). The block was deformed after 3:30 min, cleaned with isopropanol and then stored in deionized water in an oven at 40° C. for 12 hours to complete the curing. The block was removed and wiped dry with a paper towel.

[0530] Preparation of grinding blocks (II)

[0531] A commercially available CAD / CAM material based on the thermoplastic material polyetheretherketone - PEEK (breCAM BioHPP Fa. Bredent / #420121) was used. The material was cut into (18 mm*14 mm*12 mm) size.

[0532] Fabrication of preformed crowns

[0533] The grinding blocks (I), (II), (III) and (IV) were glued to the grinding machine stand (Lava TM framework).

[0534] The crown (I) with a crown design of 300 μm wall thickness was milled using a dry mill (Lava TM CNC 500-H004) is ground from grinding block (I).

[0535] The crowns (II) with a crown design of 300 μm wall thickness were milled using a dry mill (Lava TM CNC 500-H004) is ground from grinding block (II).

[0536] The crowns (III) with a crown design of 300 μm wall thickness were prepared as described above using a dry mill (Lava TM CNC 500-H004) ground from grinding block (III).

[0537] Crowns with a 300 μm wall thickness crown design (IV) - as described above - were milled using a dry mill (Lava TM CNC 500-H004) ground from grinding block (IV).

[0538] The inner surfaces of the crowns (I), (II), (III) and (IV) were roughened by sandblasting with Al2O3 powder.

[0539] Preparation of teeth

[0540] Following the manufacturer's instructions for the preparation of 3M Oral Care stainless steel crowns from 3M ESPE, the crowns were placed on a tooth model (Frasaco TM Artificial teeth (Frasaco AK-6 / 2) TM AK-6 / 2ZE-85).

[0541] Fastening test

[0542] The fit of crowns (I) and (II) on the prepared tooth stumps was tested manually. Both crowns were sufficiently flexible and showed the desired snap-fit ​​behavior for the prepared teeth.

[0543] Pull-off force test

[0544] Additional artificial teeth were prepared from brass by dry milling following the preparation guidelines set forth by the manufacturer of 3M Oral Care Stainless Steel Crowns from 3M ESPE. Figure 4 A cross section of the prepared tooth is shown in .

[0545] The surface of the artificial tooth was roughened by sandblasting with Al2O3 powder to ensure better bonding to the residual root.

[0546] The following crowns were compared: crowns (I), (II), (III) and (IV); each in groups of 5 crowns.

[0547] The following commercially available dental cements were used to cement the crowns to the artificial teeth according to the instructions provided by the manufacturer and stored at 37°C under humid conditions for 24 hours: Resin-modified glass ionomer cement: Ketac TM Cem plus (3M Oral Care, 3M ESPE).

[0548] By using adhesive bonding technology (Rely TM X Unicem, 3M Oral Care, 3M ESPE) A brass pull-off bracket was cemented to the assembly (artificial tooth and cemented crown) over the occlusal area of ​​the crown.

[0549] Place the assembly including the pull-off fixture into the Instron TM The machine was used and the pull-off force (in N) was measured at a tensile loading rate of 1 mm / min until the bond cracked. The standard deviation is given in brackets.

[0550] result

[0551] Crown (I) Crown(II) Crown (III) Crown (IV) 465.18(+ / -56.88) 143.36(+ / -22.70) 296.85(+ / -182.63) 381.29(+ / -85.19)

[0552] Figure 5 The results of the pull-off test are also shown in FIG.

[0553] Compared to the preformed crown made of thermoplastic material PEEK - Crown (II) proposed in US 8,651,867 B2 (Zilberman), the preformed composite crown (Crown (I)) as described herein shows better adhesion to the artificial tooth stump.

[0554] The preformed composite crown (crown (I)) as described herein also exhibited better adhesion to artificial tooth stumps than preformed crowns made from formulations (III) and (IV).

[0555] Elastic modulus

[0556] Furthermore, the elastic modulus (in GPa) was determined. The standard deviation is given in brackets.

[0557] result

[0558] Recipe (I) Formula (III) Formula (IV) 3.360(+ / -0.0679) 3.500(+ / -0.178) 3.630(+ / -0.144)

[0559] The elastic modulus of formulation (I) used to prepare the preformed composite dental crown (crown (I)) as described herein is lower than the elastic modulus of formulations (III) and (IV) used to prepare preformed composite dental crowns (III) and (IV).

Claims

1. A preformed composite dental crown characterized by its shape and chemical composition, The shape is characterized as follows: For molars and premolars, they have an occlusal top surface and a coronal wall defined by side surfaces: buccal, mesial, distal and lingual surfaces, wherein the buccal, mesial, distal and lingual surfaces together form a coronal wall and a coronal neck, For anterior teeth and incisors, it has a distal top surface and a coronal wall defined by side surfaces: a labial surface, a mesial surface, a distal surface and a lingual surface, wherein the labial surface, the mesial surface, the distal surface and the lingual surface together form a coronal wall and a coronal neck, in: The crown wall is characterized in that the wall thickness at the crown neck does not exceed 0.6 mm, At least two of the opposing side surfaces have a concave shape resulting in an undercut; and The chemical composition comprises: an amount of 20% to 70% by weight of nanofillers, an amount of 20% to 75% by weight of a resin matrix, The resin matrix comprises urethane (meth) acrylate, which is represented by one or more of the following urethane (meth) acrylates: as well as a (meth)acrylate not containing a urethane moiety, the (meth)acrylate not containing a urethane moiety comprising ethoxylated bisphenol A dimethacrylate, wherein the chemical composition is in a hardened state, Weight % is relative to the weight of the chemical composition, The preformed composite crown is configured to be snap-fitted onto a given tooth structure and secured to the tooth structure via an undercut.

2. The preformed composite dental crown of claim 1, wherein the shape is further characterized by at least one, more, or all of the following features: The crown wall is characterized by a wall thickness of 0.1 mm to 0.4 mm; The top surface is characterized by a wall thickness of 0.15 mm to 1.5 mm; The undercut is larger than 0.2 mm.

3. The preformed composite crown according to claim 1, wherein the nanofiller comprises particles of SiO2, ZrO2, Al2O3 or a mixture thereof.

4. The preformed composite dental crown of claim 1, wherein the nanofiller comprises aggregated, agglomerated, discrete nanoscale particles or a mixture thereof.

5. The preformed composite dental crown of claim 1, wherein the (meth)acrylate not comprising a urethane moiety is characterized as follows: The molecular weight ranges from 170 g / mol to 3,000 g / mol, Contains at least 2 polymerizable moieties.

6. The preformed composite dental crown of claim 1, wherein the chemical composition of the composite dental crown does not include any or all of the following components: An amount of a polymerizable component (w) having an acidic group greater than 2% by weight; Amounts greater than 5% by weight of solvent; The weight % is relative to the weight of the composite crown.

7. The preformed composite crown according to claim 1, wherein the chemical composition of the composite crown comprises an amount of 20 wt % to 70 wt % of a nanofiller selected from aggregated, agglomerated or discrete nanoparticles and mixtures thereof, urethane (meth)acrylate in an amount of 3 to 20% by weight, an amount of 5 to 55 wt. % of a (meth)acrylate not comprising a urethane moiety, The weight % is relative to the weight of the chemical composition of the composite crown.

8. The preformed composite dental crown of claim 1, wherein the chemical composition of the composite dental crown is characterized by any one or a combination of the following parameters: Flexural strength: 50MPa to 200MPa or 80MPa to 150MPa determined according to ISO 4049:2009, Modulus of elasticity: 1,000 MPa to 4,000 MPa determined according to ISO 4049:2009 in combination with DIN EN 843-2:2007; Impact strength: 5 kJ / m determined according to DIN 53453:175-05 2 Up to 15kJ / m 2 , Wear: less than about 20mm 3 or less than 15mm 3 or less than 10mm 3 , Color: Tooth color.

9. The preformed composite dental crown according to claim 2, wherein the composite dental crown is characterized as follows: a urethane (meth)acrylate having at least 2 polymerizable moieties is present in an amount from 3 wt % to 20 wt %, and a (meth)acrylate having at least 2 polymerizable moieties but not comprising a urethane moiety is present in an amount of 5 to 55 weight percent, Weight % is relative to the weight of the chemical composition, The chemical composition in the hardened state is characterized by the following parameters: Impact strength: 5 kJ / m determined according to DIN 53453:175-05 2 Up to 15kJ / m 2 , Modulus of elasticity: 1,000 MPa to 4,000 MPa determined according to ISO 4049:2009 in conjunction with DIN EN 843-2:2007.

10. A kit of parts comprising a set of preformed composite dental crowns according to any one of the preceding claims, the preformed composite dental crowns being distinguishable from each other by any of the following: shape, colour, size or a combination thereof.

11. The kit of claim 10, further comprising a dental cement and optionally a dental composite.

12. The kit of claim 11, wherein the dental cement is a resin-modified glass ionomer cement, a self-adhesive resin cement, or an adhesive resin cement.

13. A preformed composite crown, the composite crown being used in a method for treating a tooth, the method comprising the following steps: The preformed composite dental crown according to any one of claims 1 to 9 is fixed to the surface of a prepared tooth in the patient's mouth by using a dental cement.

14. A method for producing a preformed composite crown according to any one of claims 1 to 9, the method being carried out by any one of the following methods: Applying additive manufacturing technology, Applying molding technology, The preformed composite crown is ground from a grinding block.

Citation Information

Patent Citations

  • Process for polymerizing or copolymerizing vinyl compounds and unsaturated polyesters

    DE1495520A1

  • 1,2,6-Thiadiazine-3,5-dione-1,1 dioxides and their use

    EP0059451A1

  • (Meth)acrylic acid esters and their use in the preparation of dental masses

    EP0235826A1

  • Urethane di(meth)acrylate derivatives of 1,3-bis(1-isocyanato-1-methylethyl)benzene

    EP0934926A1

  • Radically curable urethane prepolymers and their use in dental materials

    EP1242493B1